Transmitting the Transition: Media Events and Post-Apartheid South African National Identity - Evans, Martha (Centre for Film and Media Studies, 2023)
South Africa came late to television, and its enjoyment of the medium was diminished by the fact that just as a national television service was acquired, the rest of the world began to shun the country because of apartheid. While the ruling National Party feared the integrative effects of television, they did not foresee the negative impact that exclusion from globally unifying broadcasts would have on political rule. Television helped to facilitate the sporting and cultural bans and played an important, mostly unexamined role in the transition to democracy. While South Africa was barred from participating in some of television's greatest global attractions (including sporting events such as the Olympics and contests such as Miss World), with the release of Nelson Mandela from prison – one of the world's most memorable media events – came a proliferation of large-scale live broadcasts that attracted the gaze and admiration of the rest of the world. At the same time, the country was permitted to return to international competition, and its readmittance played out on television screens across the world. These events were pivotal in shaping and consolidating the country's emerging post-apartheid national identity. Using Dayan and Katz's theory of “media events” – those historic and powerful live broadcasts that mesmerise mass audiences – this thesis assesses the socio-political effect of live broadcasting on South Africa's transition to democracy and the effects of such broadcasts on post-apartheid nationhood. The thesis follows events chronologically and employs a three-part approach: firstly, it looks at the planning behind some of the mass televised events, secondly, it analyses the televisual content of some of the events; and thirdly it assesses public responses to events, as articulated in newspapers at the time. Live broadcasting was used first by the rest of the world as a means of punishing apartheid South Africa and then by the emerging NP–ANC alliance as a means of legitimating the negotiation process. In particular, media events served as a powerful means of securing support for the country's first democratic president, Nelson Mandela. At the same time, the apparent transparency of live broadcasting helped to rejuvenate the poor reputation of the South African Broadcasting Corporation, perceived as a government mouthpiece under apartheid and, like South Africa itself, in need of an image overhaul. The thesis argues that just as print media had a powerful influence on the development of Afrikaner nationalism, so the “liveness” of television helped to consolidate the “newness” of the post-apartheid South African national identity.